2020
DOI: 10.1038/s41467-020-17510-z
|View full text |Cite
|
Sign up to set email alerts
|

Observation of topological transport quantization by dissipation in fast Thouless pumps

Abstract: Quantized dynamics is essential for natural processes and technological applications alike. The work of Thouless on quantized particle transport in slowly varying potentials (Thouless pumping) has played a key role in understanding that such quantization may be caused not only by discrete eigenvalues of a quantum system, but also by invariants associated with the nontrivial topology of the Hamiltonian parameter space. Since its discovery, quantized Thouless pumping has been believed to be restricted to the lim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 45 publications
0
52
0
Order By: Relevance
“…At last, we emphasize that, in order to achieve a reasonable adiabatic regime, the number of stacks in our experimental set-ups is appreciable and, whereas this is perfectly fine for demonstration purposes, it will be an obstacle for practical applications. Recently, Fedorova et al 59 showed that the non-adiabatic effects can be compensated using modulated dissipative channels and that such a strategy can be used to achieve quantized topological pumping with fast-driven cycles. It will be interesting to explore if this strategy can be deployed for our acoustic crystals in order to reduce the number of stacks needed for the topological pumping of sound.…”
Section: Discussionmentioning
confidence: 99%
“…At last, we emphasize that, in order to achieve a reasonable adiabatic regime, the number of stacks in our experimental set-ups is appreciable and, whereas this is perfectly fine for demonstration purposes, it will be an obstacle for practical applications. Recently, Fedorova et al 59 showed that the non-adiabatic effects can be compensated using modulated dissipative channels and that such a strategy can be used to achieve quantized topological pumping with fast-driven cycles. It will be interesting to explore if this strategy can be deployed for our acoustic crystals in order to reduce the number of stacks needed for the topological pumping of sound.…”
Section: Discussionmentioning
confidence: 99%
“…In the adiabatic driving limit and within a Markov-Lindblad framework, the inclusion of external noise and dissipation stabilizes the conversion effect as the system approaches a steady state with a quantized number of emitted photons per driving period 26 . In the nonadiabatic limit, it was recently demonstrated that the introduction of a non-Hermitian tailored time-periodic dissipation restores the topological transport quantization of Thouless pumps in plasmonic waveguide arrays, emphasizing the uniqueness of Floquet topological systems 58 In this Appendix we provide further details on the frequency conversion effect. In Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, one has a potential of utilizing the disorder in order to engineer new states of matter, where the many-body localized phase is a recent prominent example [4,5], which is currently being debated [6]. This is in line with an ongoing quest to exploit the system environment as a tunable knob for quantum control [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 91%